Summary of the CAADP Strategy and Action Plan (2026-2035) - African Union Development Agency , NEPAD (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This brief provides a summary of the new Comprehensive Africa Agriculture Development Programme (CAADP) Strategy and Action Plan (2026-2035). It outlines the CAADP vision and guiding principles and describes the identified trends and drivers of Africa’s agrifood systems. It presents the new results chain and details the six strategic objectives, priority interventions, actions, outputs and outcomes. The final sections of the brief describe proposed means for strengthening CAADP coordination and implementation, resourcing the CAADP Strategy and Action Plan, establishing a robust knowledge and support system and improving CAADP communication and advocacy.